2017
DOI: 10.1021/acs.jmedchem.7b00179
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis, Antiviral Potency, in Vitro ADMET, and X-ray Structure of Potent CD4 Mimics as Entry Inhibitors That Target the Phe43 Cavity of HIV-1 gp120

Abstract: In our attempt to optimize the lead HIV-1 entry antagonist, NBD-11021, we present in this study the rational design and synthesis of 60 new analogues and determination of their antiviral activity in a single-cycle and a multicycle infection assay to derive a comprehensive structure-activity relationship (SAR). Two of these compounds, NBD-14088 and NBD-14107, showed significant improvement in antiviral activity compared to the lead entry antagonist in a single-cycle assay against a large panel of Env-pseudotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 73 publications
3
103
0
2
Order By: Relevance
“…We evaluated those compounds against a selection of 34 HIV-1 clones of clinical isolates of subtypes A, B, C, and D and of recombinant subtype A (A rec ), including A1/D, A2/D, and AG. We compared the three selected compounds with the previously described compound NBD-14113 [13] . We found that the three polycyclic compounds exhibited anti-HIV-1 activity at low micromolar concentrations, with overall mean IC 50 values very similar to that of NBD-14113 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated those compounds against a selection of 34 HIV-1 clones of clinical isolates of subtypes A, B, C, and D and of recombinant subtype A (A rec ), including A1/D, A2/D, and AG. We compared the three selected compounds with the previously described compound NBD-14113 [13] . We found that the three polycyclic compounds exhibited anti-HIV-1 activity at low micromolar concentrations, with overall mean IC 50 values very similar to that of NBD-14113 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We used NBD-556 (an HIV-1 entry agonist [13, 15] ) as a control. Although NBD-556 enhanced the infection of the Cf2Th-CCR5 cells, we found that none of the new polycyclic NBD compounds enhanced HIV-1 infectivity in those cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The available crystal structure of a gp120 protein with ligand 82M will be taken from protein data bank (PDB id 5U6E) 15 . The parameters and missing hydrogen for gp120 were prepared using LEAP module of AMBER package 16 using amber ff12SB force filed.…”
Section: Methodsmentioning
confidence: 99%
“…As suggested from the x-ray structure of NBD-11021, it bounds to HIV-1 env gp120 and gives rise to a conclusion that this molecule binds to the Phe43 cavity 14 . The energetic contribution of each amino acid was verified at the binding site involved in stabilizing the complex, ( PDB: 5U6E) 15 …”
Section: Introductionmentioning
confidence: 99%